Calculating the fluxes of atmospheric neutrinos - Cook, L (2022)
The study of neutrinos produced in the interaction of cosmic rays with atmospheric nuclei was instrumental to the discovery of neutrino oscillations. As neutrino physics now enters the precision measurement era, precise measurement of atmospheric neutrino oscillations remains of interest due to its ability to answer questions such as the extent of CP violation in the neutrino sector and the ordering of the neutrino masses. An analysis of neutrino oscillations involves a comparison between the neutrino flux measured by a detector such as the Super-Kamiokande detector in Japan and the neutrino flux expected in the absence of oscillations. This thesis presents an estimate for the un-oscillated atmospheric neutrino flux using the Bartol atmospheric Monte Carlo simulation. The previous iteration of the Bartol flux estimate released in 2004 found that the dominant sources of systematic uncertainty on the neutrino flux were the uncertainty of the flux of cosmic rays and uncertainties in hadron production during the interaction of those cosmic rays with the atmosphere. Within this thesis, measurements of hadron production by fixed target experiments are used to develop a dataset- driven model which is applied to the simulation of pion and kaon production in atmospheric showers. The significant fraction of the relevant hadron production phase space covered by the datasets released since 2004 allows, for the first time, a calculation of the neutrino flux with hadronic interactions predominantly based on dataset measurements rather than Monte Carlo prediction. Additionally, an updated parameterisation of the cosmic ray fluxes is included within the neutrino flux calculation with parameters obtained in a global fit to recent cosmic ray flux measurements. The uncertainty of the atmospheric neutrino flux has been evaluated when using the updated hadronic interaction and cosmic ray flux models. The νμ flux uncertainty has been found to decrease from ∼15% estimated on the 2004 fluxes to ∼5-10% in this updated flux estimate.